Numerical investigation of the stress concentration on 7075-T651 aluminum alloy with one or two hemispherical pits under uniaxial or biaxial loading. (May 2019) - Zuñiga Tello, Ishvari F.; Domínguez Almaraz, Gonzalo M.; López Garza, Víctor; Guzmán Tapia, Manuel
Highlights: Numerical results for stress concentration on hemispherical pits. Stress concentration in function of pits separation and plate thickness. Uniaxial and biaxial loading on aluminum plates with one or two pits. Confrontation between uniaxial and biaxial loading. Stress evolution for two pits, following perpendicular and longitudinal paths. Abstract: Numerical simulations were carried out in order to obtain the stress concentrations induced by simulated hemispherical pits with 500 µm of diameter on square plates of 100 mm 2 of the aluminum alloy 7075-T651, for three different plate thickness: 0.7, 1.6 and 3 mm. The pertinence of this study is supported by the fact that modern industries using this aluminum alloy, such as the aeronautical, marine, mold tool manufacturing and arms industries, are affected by the combination of loading and corrosion, which leads to stress concentration and the failure of material. Numerical simulations were performed to investigate the effect of one and two pits on the surface of aluminum plates, for the transverse or longitudinal load orientation and under uni-axial and biaxial loading. In addition, the depth of the pits across the thickness of the plate together with the proximity of two pits under the last described conditions were investigated. It was found that the orientation of two pits in regards the applied load plays a significant role on the stress concentration under uniaxial loading. Finally, graphs for the stress concentration and the corresponding general tendencies were obtained associated with hemispherical pits and the mentioned parameters of the plates, together with the general conclusions concerning these numerical results.